Post-financial Crisis Times: Only a Short Phase of Re-intermediation and Re-direction to Boring Banking Business Models? Regulatory Burden, Fintech Competition and Concentration Processes - Karl-Peter Schackmann-Fallis; Mirko Weiß (Vierteljahrshefte zur Wirtschaftsforschung, 2018)
The analysis highlights the aspects of diversified market structures and of local, low-distance banking as advantageous for financial stability. Heterogeneity protects from uniform market behaviour. Local banking can better overcome the problem of asymmetric information, particular in SME lending. Moreover, connections to other socio-political aspects must be factored into the assessment: financial inclusion, presence in rural areas, and depletion of regional disparities. The vast regulation and Europeanisation of supervision, however, - so far neglecting differences in risk profiles and bank sizes - have imposed a higher minimum business size, which led to an extensive merger trend, especially negatively affecting smaller and regionally focussed credit institutions. So it seems that the process of re-intermediation and re-directing banking business back to deposit-based lending, taken place in the aftermath of the financial crisis, was of short length only. Regarding recent developments, we argue that FinTech applications are expected to complement, not to replace, existing banking and financial services. However, we warn against existing regulatory loopholes and regulatory arbitrage for FinTech applications and BigTech approaches. – – Die Analyse beleuchtet die Aspekte diversifizierter Marktstrukturen sowie regional ausgerichteter Geschäftsmodelle als vorteilhaft für Finanzstabilität. Heterogenität schützt vor gleichgerichtetem Marktverhalten. Regionale Kreditinstitute können das Problem asymmetrischer Informationen besser überwinden, insbesondere bei der Kreditvergabe an KMU. Darüber hinaus sind weitere gesellschaftspolitische Aspekte in die Bewertung einzubeziehen: finanzielle Einbindung, Präsenz in ländlichen Gebieten und der Abbau regionaler Disparitäten. Die umfangreiche Regulierung und Europäisierung der Aufsicht – bislang unter Vernachlässigung von Unterschieden im Risikoprofil und Institutsgrößen – erzwang jedoch eine höhere Mindestinstitutsgröße, was zu einem umfassenden Fusionstrend führte, der insbesondere kleinere und regional ausgerichtete Kreditinstitute negativ traf. Es scheint daher, dass der Prozess der Re-Intermediation und Wiederausrichtung des Bankgeschäfts auf einlagenbasierte Kreditvergabe, der nach der Finanzmarktkrise zu beobachten war, nur kurz währte. In Bezug auf jüngere Entwicklungen argumentieren wir, dass FinTech-Anwendungen vorhandene Bank- und Finanzdienstleistungen ergänzen, aber nicht ersetzen werden. Wir warnen jedoch vor bestehenden Regelungslücken und Möglichkeiten regulatorischer Arbitrage für FinTech-Anwendungen und BigTech-Ansätze.
Keywords: D82; E51; G14; G21; G28; L11; O16; 330; Financial intermediation; business models of banks; regional development; small- and medium-sized enterprises; financial regulation; fintechs